ERP systems implementation in Malaysia: the importance of critical success factors - Jafari, Seyed Mohammadbagher; Osman, Mohd Rasid; Mohd. Yusuff, Rosnah; Tang, Sai Hong (Federation of Engineering Institutions of Islamic Countries, 2006)
In order to survive in a rapidly changing business environment, organizations must improve their own business practices and procedures. Enterprise resource planning (ERP) systems can be considered as the most important development in the corporate use of information technology and are beginning to be the backbone of organizations. The difficulties and high failure rate in implementing ERP systems have been widely cited in the literature. Factors affecting ERP implementation are complex and abundant and numerous authors have identified a variety of factors that can be considered to be critical to the success of an ERP implementation. In this paper, the critical factors that affect ERP systems implementation success in Malaysia have been identified and the importance of these factors have been investigated. Through a comprehensive review of the literature, 10 factors were found to be critical to ERP implementation success. The importance of these factors was investigated within Malaysian companies using questionnaire survey method. “Top management support” and “Clear goals and objectives” have been shown to be the extremely important factors for ERP implementation in Malaysia.